Familial partial trisomy 8p without dysmorphic features and only mild mental retardation - Engelen, J J M (1995)
We report on a mother and her two sons who had a direct duplication of chromosome region 8p22-8p23.1 without dysmorphic features and only mild mental retardation. The patients have been studied using G banding, chromosome painting, and FISH using cosmid probes specific for the region 8p23.1-8pter. Comparison of the phenotypes of our patients and of published patients with an inversion duplication of the short arm of chromosome 8 indicates that trisomy for chromosome band 8p21 causes the more severe clinical picture in the latter.